Chapter Introducing Asian Sound Cultures - Haukamp, Iris (Taylor & Francis, 2023)
In this brief introduction we highlight the importance of broadening the cartography of sound studies beyond the West. Over the last decade or so, the geographical range of sound studies has rapidly broadened at the same time as keywords and approaches to sound in the humanities and social sciences have become increasingly standardised theoretical and conceptual tools. The need to explore ways of thinking about sound articulated by experiences outside the West is becoming essential to ensuring the field remains as open to interpretation and as diffuse in nature and geography as the object of study itself. In this introduction we outline the contributions to this project made by the chapters gathered in this volume. We argue that mixing historical perspectives with ethnography, literary studies, film studies, technology, language and music and listening for the inflections driven by sonic regimes imposed by a global process of change in Asia can help us to better understand the shared experience and construction of modern sound. We also argue for an 'international localism' that, whilst accepting that the sound of modernity is inseparable from the process of modernity, amplifies the ambiguity of modern understandings of sound and mobilises the diverse historical experiences and rich social practices of Asia to provide alternative horizons for the exciting and vibrant field of sound studies.